Monte Carlo Simulation Application for Project Scheduling Improvements in The Shipping Industry - Nazaruddin, Nazaruddin; Arini Anestesia Purba; I Putu Deny Arthawan Sugih Prabowo (SAGA: Journal of Technology and Information System, 2024)
This research was carried out at PT. X is a shipping yard that produces one of them, namely ship blocks. In the implementation of ship block building projects, there is uncertainty in the project's duration, so it needs to be completed by applying the Monte Carlo simulation method. Monte Carlo Simulation is a method used to model and analyze systems with risks and uncertainties. The basis of the Monte Carlo simulation is to conduct experiments on probabilistic elements through random sampling. This study aims to identify the probability of duration and percentage of possibility of the period in a project so that scheduling using Microsoft Project software is more measurable and optimal. Based on the Monte Carlo simulation results in ball software, the fastest duration for the H402 ship block project was obtained, namely 64 days, with a 0% probability of success. The longest time was 83 days with a chance of 100%, and the average duration for 73 days with a possibility of 65%, while the plan duration was 80 days with a probability of 94.7%. Then for the H501A block work, the fastest time produced is 74 days with a chance of 0%, the longest most extended is 82 days with a probability of 100%, and the average duration for 79 days with a possibility of 60-70% while the time of the plan is for 75 days with a probability of 9.8%.